The displacement simulation for cracked earth structure with different geometry - Namdar, Abdoullah; Berto, Filippo; Nurmunira, Muhammad (Elsevier B.V., 2022)
The strength of the material and safe economical design are important from the design point of the view in all branches of engineering. In many regions, the geographical characteristics of territory play important role in the design geometry of the backfill. In addition, using clayey soil to construct backfill results to have a crack in the cracked zone of the backfill. In the present study, the geometry of two different clayey soil backfill was investigated. The main aim of this study is for understanding the impact of the geometry of the model on the nonlinear displacement of the clayey soil backfill when the seismic load with equal magnitude is applied on the modelled clayey soil backfill. The results illustrate the seismic response and nonlinear displacement of the clayey soil backfill were modified by changing the geometry of the model. In point of view, to construct clayey soil backfill in a site needs to use different soil in constructing each clayey soil backfill concerning the geometry of the model. The novelty of this work introduces the concept of strength of the material association with the crack and geometry of the model in seismic design of the clayey soil backfill, considering the nonlinear displacement of the model in loading and reloading stages. Moreover, illustration of the nonlinear strain and nonlinear displacement of the model. The outcome of this investigation importantly explains the impact of model geometry in the cracks interaction, distribution of the displacement of the model, and displacement magnitude